2010
DOI: 10.1055/s-0030-1258361
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of Some 2-Substituted Melatonin Derivatives

Abstract: A simple strategy for the synthesis of some 2-substituted melatonin derivatives using p-anisidine as starting material is reported. The key step is a chemoselective reduction of a cyano group in the presence of an appropriate acid anhydride by hydrogenation over Adams' catalyst or with sodium borohydride in the presence of catalytic amounts of anhydrous nickel(II) chloride. The 2-substituted melatonin derivatives were obtained in six or seven steps from inexpensive p-anisidine in 9-13% overall yield.Melatonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Selective nitrile reduction in the presence of cyclic amide was also achieved using NaBH 4 in methanol in the presence of catalytic amounts of anhydrous NiCl 2 . We have previously shown that the addition of acetic anhydride to the reduction mixture could obtain 2-chloromelatonin 7d [ 26 ] with good yield ( Scheme 6 ). In this work, we demonstrated that the same reduction followed by one-pot acylation can be used in the case of 2-oxindole derivatives and other anhydrides ( Scheme 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective nitrile reduction in the presence of cyclic amide was also achieved using NaBH 4 in methanol in the presence of catalytic amounts of anhydrous NiCl 2 . We have previously shown that the addition of acetic anhydride to the reduction mixture could obtain 2-chloromelatonin 7d [ 26 ] with good yield ( Scheme 6 ). In this work, we demonstrated that the same reduction followed by one-pot acylation can be used in the case of 2-oxindole derivatives and other anhydrides ( Scheme 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The following isatin derivatives were obtained by N -alkylation using previously described procedure [ 28 ]: N -methylisatin 1e , N -benzylisatin 1f , N -methyl-5-methoxyisatin 1g , N -benzyl-5-methoxyisatin 1h , N -methyl-5-bromoisatin 1i , N -methyl-6,7-dimethylisatin 1j . The following compounds were obtained as previously described: cyano(2-oxoindolin-3-ylidene)acetic acid 2a [ 25 ], cyano(2-oxo-5-methoxy-indolin-3-ylidene)acetic acid 2b [ 24 ], cyano(2-oxo-5-bromoindolin-3-ylidene)acetic acid 2c [ 23 ], 2-(2-oxo-2,3-dihydro- 1H -indol-3-ylidene)acetonitrile 3a , [ 25 ] 2-(1-methyl-2-oxo-2,3-dihydro- 1H -indol-3-ylidene)acetonitrile 3e [ 24 ], 2-(5-methoxy-1-methyl-2-oxo-2,3-dihydro- 1H -indol-3-ylidene)acetonitrile 3g [ 29 ], 2’-oxo-1’,2’-dihydrospiro[cyclopropane-1,3′-indol]-3-carbonitrile ( 6a ) [ 19 ], 5′-methoxy-2’-oxo-1’,2’-dihydrospiro[cyclopropane-1,3′-indol]-3-carbonitrile ( 6b ) [ 19 ], 2-chloromelatonin 7d [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The following ones belong to the MLT compound library of Les Laboratoires Servier. Their respective syntheses were previously reported as indicated in the following list: S 22153 (Legros et al, 2019); SD 1883 (Legros et al, 2019); SD 1918 (Legros et al, 2014b); S 27128 (Leclerc et al, 2002); S 22958 (Leclerc et al, 1998); S 73229 (Lozinskaya et al, 2011);S 70643 (Ettaoussi et al, submitted manuscript);andSD 1671 (Harth e et al, 2003). All compounds were dissolved in DMSO at a stock concentration of 10 mM and stored at À20 C.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, the reactivity of a series of model druglike molecules was evaluated under our optimized reaction conditions (Scheme ). The direct synthesis of the vinburnine SCF 3 analogue 4 and a precursor of the trifluoromethylthiolated analogue of melatonin 6 were selectively achieved . To evaluate the ability to extend our strategy to aromatic steroids, the protected 4‐methylphenol model substrate 7 was submitted to the optimized reaction conditions and led to the exclusive formation of 8 in 64 % yield.…”
Section: Methodsmentioning
confidence: 99%